Performance Of Tio2 Via Screen Printing Technique - Zamberi, Nur Faziera Natasha (Universiti Sains Malaysia, 2017)
Nanostructured single layered of pure titanium dioxide, TiO2 with different composition of paste thick films have been fabricated by screen printing technology on an alumina substrate. The composition of paste are the TiO2 film at mass ratio of [TiO2]:[(CH2OH)2] = 3:7 , TiO2 film at mass ratio of [TiO2]:[(CH2OH)2] = 5:5 and TiO2 film at mass ratio of [TiO2]:[(CH2OH)2] = 6:4 .The pastes used for film preparation were obtained by adding an organic vehicle ethylene glycol, (CH2OH)2 to the oxide powders together. Samples were dried up to 100 °C and calcined at 350 °C/60 minutes. Different composition have been used to study the effect of composition of paste towards the sensitivity of sensor. The fabricated gas sensors were also used to test their responses to different operating temperatures (150 – 400 °C). The results showed that the optimum operating temperature for the synthesised gas sensor is at 200o C. Structural, morphological and optical studies have been carried out using Scanning Electron Microscopy (SEM) analyses, X-Ray Diffraction (XRD) and Energy Dispersive X-Ray (EDX) analysis spectroscopy. The SEM characterization shows the presence of porosity for the TiO2 particles while EDX confirms the chemical composition of TiOx to be TiO2. The XRD result indicates that the crystallite size increases as the particle size increase and TiO2 structure is anatase phase. Overall, the sensor fabricated by using mass ratio of [TiO2] :[(CH2OH)2] = 5:5 illustrates the best sensing performance with the highest sensitivity. These findings were analysed and discussed by correlating the experimental results with the characterization analysis which were closely related to the properties of the sensing materials.